Impact of temperature variations on burden of lower respiratory infections under climate change (1990–2021) - Weiqi Huang; Long Yin; Hongyu Li; Wangxuan Yang; Shiying Huang; Liuying Wang; Kexin Wang; Yanhua Hao; Qunhong Wu; Huan Liu (BMC Public Health)
Abstract Objectives We aimed to evaluate the global burden and trends of lower respiratory infections (LRIs) attributable to non-optimal temperatures between 1990 and 2021, focusing on age, period, and cohort effects as well as health inequalities to inform targeted public health policies. Methods Using the Global Burden of Disease 2021 database, we obtained the age-standardized mortality rate (ASMR) and disability-adjusted life-years rate (ASDR) for LRIs related to non-optimal temperatures. We calculated estimated annual percentage changes (EAPC) to assess LRIs burden trends and applied age-period-cohort modeling to quantify age, period, and cohort effects. Health inequalities were evaluated using the slope index of inequality and the concentration index. Results In 2021, the highest ASDR for LRIs due to high temperatures occurred in children under 5 (347.66/100,000), whereas the highest ASMR for LRIs due to low temperatures occurred in adults aged ≥ 65 (338.49/100,000). Globally, the LRIs burden from non-optimal temperatures declined (EAPC: ASMR –2.48; ASDR –3.33). However, among the five climate zones, the LRIs burden in the boreal zone due to high temperatures increased (EAPC: ASMR 24.14; ASDR 45.14), whereas all other climate zones showed decreasing trends. In lower Sociodemographic Index (SDI) regions, the high-temperature–related LRIs burden was more pronounced. Relative inequities driven by non-optimal temperatures worsened in low-SDI regions. Conclusion From 1990 to 2021, the global burden of LRIs attributable to non-optimal temperatures declined overall; however, high-temperature–related LRIs increased in boreal zones. These health inequalities underscore the urgent need for targeted climate adaptation policies, such as providing international assistance, improving infrastructure, offering healthcare resources, and promoting vaccine coverage, particularly for vulnerable populations in low-SDI regions and boreal zones.